Crowdfunding as a new funding alternative for early stage start-ups - Rantala, Valtteri (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Attracting outside capital is a common problem for start-up companies. Capital markets define the funding options for companies and firms which suffer the most from these capital market imperfections are small start-up companies. Therefore it is important to study any new funding model which can offer a new solution to this inefficiency of capital markets. This study explains the traditional funding models for start-ups such as founders, friends & family, banks, business angels and venture capitalist. After giving background to traditional start-up funding this study delves into crowfunding (CF) and introduces it as a new funding method. The objective of the thesis is to answer one broad research question: Why and how should start-up companies use CF as an alternative funding method? To properly delve into this, this question has the following sub-questions: What kind of funding alternatives do start-up companies have? What are the pros and cons of CF compared to other funding options? How can start-ups benefit from CF? This study gives background on the rise of CF and the reasons why this new model is needed. Author will explain the different components of CF such as platforms, crowdfunders and projects. Also benefits and challenges of the crowdfunding model are investigated. As a new funding model CF has had to clear out many obstacles from its way. These are, for example, legal and regulatory issues as well education of crowd investors to understand this new investment option. . Start-up entrepreneurs can gain valuable insight from this study. The author has attempted to form best practices and guidelines of how to operate in the CF environment. This study was conducted by performing expert interviews, collecting data from previous studies and performing a content analysis of successful crowdfunding cases. Main findings from the study were that CF has huge potential in funding entrepreneurial projects. It is still a niche way for funding but growing rapidly. CF is earning its place among traditional funding options and has potential to fund projects which otherwise would struggle to find funding. With CF entrepreneur can tap into geographically diverse audience. It is a powerful validation tool for products and ideas and has the power to bring democratic elements to entrepreneurial funding.